Lake salinization on the Qinghai–Tibetan Plateau alters viral community composition and lifestyles - Yuan-Guo Xie; Yan-Ling Qi; Zhen-Hao Luo; Yan-Ni Qu; Jian Yang; Shi-Qiang Liu; Hai-long Yang; Dan-Wei Xie; Zimeng Wang; Hong-Chen Jiang; Zheng-Shuang Hua (Communications Earth & Environment)
Abstract Global warming has accelerated lake salinization, driving changes in microbial community structure and function. However, the dynamics of viral communities in response to salinity remain unclear. Here, we apply metagenomic sequencing to a lake on the Qinghai–Tibet Plateau, spanning a broad salinity gradient, to investigate viral community dynamics. Our findings reveal that salinity strongly influences viral composition and modulates viral lifestyles. Temperate viruses increase in relative abundance along the salinity gradient, whereas virulent viruses show a corresponding decline. These shifts are mirrored in the prokaryotic communities, with Alphaproteobacteria and their infecting temperate viruses, notably Casadabanvirus, becoming more prevalent in higher salinity zones. Viral genomes encode genes associated with osmotic stress adaptation, DNA recombination, and nutrient transport, which may facilitate host adaptation to saline stress. This study provides valuable insights into the interplay between viral and prokaryotic communities in response to lake salinization.